Extraction and isolation of pectin rich in homogalacturonan domains from two cultivars of hawthorn berry (Crataegus pinnatifida). (April 2021) - Roman, Laura; Guo, Mengmeng; Terekhov, Anton; Grossutti, Michael; Vidal, Natalia P.; Reuhs, Bradley L.; Martinez, Mario M.
Abstract: Hawthorn berries present high pectin content with good ability to form and stabilize oil-in-water emulsions. However, successful applications are determinant of high yield and purity as well as good surfactant properties based on their molecular structure. In this work, pectins from one of the most common Crataegus pinnatifida cultivars (Dajinxing, DA), and from a less known cultivar gaining popularity (Mianqiu, MI), were extracted and isolated. They were comparatively investigated with two commercial pectins from citrus peel [> 67.9% degree of methyl-esterification (DM) and >78% galacturonic acid (GalA)] and analyzed for their yield, molecular weight (HPSEC-MALS-RI), monomer composition and glycosyl linkage analysis (GC-MS), DM (titration, FTIR and 1 H NMR), and emulsifying performance. MI showed a 2-fold greater pectin yield (in terms of GalA) than DA (61.2% vs. 38.3%). Thus, hot acid extraction had to be followed by an enzymatic step to remove starch molecules and obtain purified DA and MI pectins (>86% GalA), which also resulted in pectin demethoxylation (DM <38%). Remarkably, purified hawthorn pectins presented lower molecular weight than commercial citrus pectins (98–126 kDa vs 164–235 kDa) together with a higher proportion of homogalacturonan (HG) domain and a significantly greater emulsifying activity and stability. Specifically, MI showed a higher HG proportion and a less branched rhamnogalacturonan-I (RG-I) domain [Branching calculated as (Arabinose + Galactose)/Rhamnose = 2.2] than DA (Branching = 3.1), with significantly shorter arabinan and galactan side chains (evidenced by more terminal arabinose and galactose). The yield and structure of MI pectin strongly indicates that MI berry is an excellent pectin source with distinguished functionality. Graphical abstract: Image 1 Highlights: Mianqiu cultivar resulted in a 2-fold higher yield of pectin than Dajinxing cultivar. Hawthorn pectins were richer in homogalacturonan than citrus pectins. Mianqiu pectin had more homogalacturonan and less branched rhamnogalacturonan-I. Enzymatic starch removal led to demethoxylation of purified pectin. Purified pectins had better potential to form and stabilize emulsions than citrus ones.